2018
DOI: 10.20882/adicciones.1067
|View full text |Cite
|
Sign up to set email alerts
|

Las transiciones en el uso de alcohol en una cohorte de nacimiento-sexo en la población general: el proyecto transversal PEGASUS-Murcia

Abstract: Resumen AbstractLas transiciones en el uso de alcohol en una cohorte de nacimiento-sexo en la población general: el proyecto transversal PEGASUS-Murcia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…This disinhibition has also been linked to engage in new sexual practices, multiple partners, and less ability to use barrier methods. In this sense, our findings support a worsening trend over the years, which is particularly worrying based on the important levels of alcohol consumption among the Spanish young people [47]. As past authors reported [37], this phenomenon could diminish their competences to decision-making about their sexual behaviors, as well as their perceived susceptibility that also affects the likelihood of being HIV tested.…”
Section: Discussionsupporting
confidence: 72%
“…This disinhibition has also been linked to engage in new sexual practices, multiple partners, and less ability to use barrier methods. In this sense, our findings support a worsening trend over the years, which is particularly worrying based on the important levels of alcohol consumption among the Spanish young people [47]. As past authors reported [37], this phenomenon could diminish their competences to decision-making about their sexual behaviors, as well as their perceived susceptibility that also affects the likelihood of being HIV tested.…”
Section: Discussionsupporting
confidence: 72%